The association between diverse psychological protocols and the efficacy of psilocybin-assisted therapy for clinical depressive symptoms: a Bayesian meta-analysis - Chen, Mu-Hong; Cheng, Shu-Li; Kao, Yu-Chen; Tseng, Ping-Tao; Hsu, Chih-Wei; Yu, Chia-Ling; Yang, Fu-Chi; Thompson, Trevor; Hsu, Tien-Wei; Liang, Chih-Sung (Frontiers in Psychiatry, 2024)
Objective: Psilocybin-assisted therapy has shown promising efficacy on clinical depressive symptoms. However, diverse psychological support or psychotherapy was performed with psilocybin treatment. This study aimed to explore the association of psychological protocols with the efficacy of psilocybin-assisted therapy for depressive symptoms.Method: Five major databases were systemic searched for clinical trials addressing psilocybinassisted therapy for patients with clinical depressive symptoms. A Bayesian random-effects metaanalysis and meta-regression were performed. The effect size was mean difference (with 95% credible interval) measured by 17-Item Hamilton Depression Rating Scale.Results: There were 10 eligible studies including 515 adult patients with clinically diagnosed depression. The psychological protocols could be categorised into four types: (i) manualized directive psychotherapy(k=1); (ii) manualized nondirective psychological support(k=3), (iii) nonmanualized nondirective psychological support(k=5); and (iv) non-manualized supportive psychotherapy(k=1). The pooled standard mean difference of psilocybin-assisted therapy was 10.08 (5.03-14.70).Compared with manualized nondirective psychological support, the other three psychological approaches did not differ significantly. The improvement of depressive symptoms was not associated with the psychological protocols in adult patients receiving psilocybin-assisted therapy.